Identity by descent and candidate gene mapping of Richieri-Costa and Pereira syndrome - de Lima, RLLF; Moretti-Ferreira, D.; Richieri-Costa, A.; Murray, J. C. (Wiley-Blackwell, 2003)
The Richieri-Costa-Pereira syndrome is a rare autosomal recessive disorder characterized by short stature, Robin sequence, cleft mandible, pre/postaxial anomalies and clubfoot. of 15 families reported with this disorder 14 are from Brazil suggesting a founder effect. We studied 15 families using identity-by-descent as a hypothesis to attempt gene localization We have examined through linkage analysis 497 polymorphicmarkers and also performed direct sequencing of exons for 10 candidate genes selected on the basis of their expression in the developing mandible and limb. No evidence for allele sharing at any locus tested or mutations in candidate genes was found. Additional higher resolution mapping, new families and other candidate genes might improve future chances of gene identification. (C) 2003 Wiley-Liss, Inc.
Keywords: Richieri-Costa-Pereira syndrome; cleft mandible; Marshfield markers